2016
DOI: 10.1002/yea.3210
|View full text |Cite
|
Sign up to set email alerts
|

Natural gene expression variation studies in yeast

Abstract: The rise of sequence information across different yeast species and strains is driving an increasing number of studies in the emerging field of genomics to associate polymorphic variants, mRNA abundance and phenotypic differences between individuals. Here, we gathered evidence from recent studies covering several layers that define the genotypephenotype gap, such as mRNA abundance, allele-specific expression and translation efficiency to demonstrate how genetic variants co-evolve and define an individual's gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 148 publications
(238 reference statements)
2
11
0
Order By: Relevance
“…However, if we focus on just one genotype, regardless of URA3 sol or URA3 agg , we obtain higher noise when uracil is added. This is consistent with the current view that the maximum population variance is achieved under conditions with no selection (Thompson & Cubillos, ). Interestingly, the cell‐to‐cell variation in protein abundance is higher in the deposits compared to the cytosol for URA3 agg irrespective of whether Ura3p is essential non‐essential or toxic (Fig C).…”
Section: Resultssupporting
confidence: 92%
“…However, if we focus on just one genotype, regardless of URA3 sol or URA3 agg , we obtain higher noise when uracil is added. This is consistent with the current view that the maximum population variance is achieved under conditions with no selection (Thompson & Cubillos, ). Interestingly, the cell‐to‐cell variation in protein abundance is higher in the deposits compared to the cytosol for URA3 agg irrespective of whether Ura3p is essential non‐essential or toxic (Fig C).…”
Section: Resultssupporting
confidence: 92%
“…There is also a positive association between galactose metabolism ability and the flower/Ipomoea isolation environment and a negative association between galactose metabolism ability and tree or insect frass isolation environments [54]. While gene gain and loss in budding yeasts may play an important role in ecological adaptation, variation in gene expression is also a likely contributor [55][56][57]. The recent publication of 332 budding yeast genomes and the identification of translational selection on codon usage in a majority of these species provide a unique opportunity to test for differences in GAL gene expression-inferred from optimal codon usage-across ecological niches inferred from recorded isolation environments [54,[58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, non-invasive nor mutagenic strategies represent an alternative where variants of interest are selected from standing natural genetic variation ( Cubillos, 2016 ). S. cerevisiae strains are genotypically and phenotypically highly variable, and thus are an ideal model for studying trait improvement ( Thompson and Cubillos, 2017 ; Peter et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although, these regions explain a substantial fraction of the natural phenotypic variation between individuals, a wide set of variants across eukaryotes are located within non-coding regions and finely modulate gene expression and ultimately phenotypes ( Wray, 2007 ). In this context, non-coding regions have been less explored in yeast and could be useful for genetic breeding and industrial applications via the modulation of gene regulation and expression ( Thompson and Cubillos, 2017 ). Previous expression profiles of S. cerevisiae isolates obtained from different ecological niches have demonstrated that the genetic control of expression is well-defined ( Fay et al, 2004 ; Kvitek et al, 2008 ; Ehrenreich et al, 2009 ; Zhu et al, 2009 ; Fraser et al, 2010 ; Cubillos et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%